Polyol-Made Spinel Ferrite Nanoparticles—Local Structure and Operating Conditions: NiFe2O4 as a Case Study - Gaudisson, T.; Nowak, S.; Nehme, Z.; Menguy, N.; Yaacoub, N.; Grenèche, J.-M.; Ammar, S. (Frontiers in Materials, 2021)
We report the effect of a polyol-mediated annealing on polyol-made nickel ferrite nanoparticles. By combining X-ray Fluorescence spectroscopy, X-ray diffraction and 57Fe Mössbauer spectrometry, we showed that whereas the as-prepared nanoparticles (NFO) are stoichiometric, the annealed ones (a-NFO) are not, since Ni0-based crystals precipitate. Nickel depletion from the spinel lattice and reduction in the polyol solvent is accompanied with an important cation migration. Indeed, thanks to Mössbauer hyperfine structure analysis, we evidenced that the cation distribution in NFO departs from the thermodynamically stable inverse spinel structure with a concentration of tetrahedrally coordinated Ni2+ of 18 at.-% (A sites). After annealing, and nickel demixing, originated very probably nickel from the tetrahedral spinel lattice of NFO, the spinel phase accommodate with cation and anion vacancies leading to the (Fe3+)A[Ni2+0.82Fe3+0.18]BO4-0.13 formula .